The Science behind the COVID Pandemic and Healthcare Technology Solutions - Adibi, Sasan; Rajabifard, Abbas; Shariful Islam, Sheikh Mohammed; Ahmadvand, Alireza; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book offers a timely review of modern technologies for health, with a special emphasis on wireless and wearable technologies, GIS tools and machine learning methods for managing the impacts of pandemics. It describes new strategies for forecasting evolution of pandemics, optimizing contract tracing, and for detection and diagnosis of diseases, among others. Written by researchers and professionals with different backgrounds, this book offers a extensive information and a source of inspiration for physiologists, engineers, IT scientists and policy makers in the health and technology sector. .
Introduction -- Pandemic$1 (Bs Behavior of One Year in Six Most Affected Countries using Polynomial Generated SIR Model -- Digital contact tracing for COVID 19: a missed opportunity or an expensive mess -- A Re-configurable Software-Hardware CNN Framework for Automatic Detection of Respiratory Symptoms -- A Comprehensive Telemedicine Service in Hong Kong Provided Through a Mobile Application -- Adapting to live in the global pandemic era: Case studies -- Towards QR code health systems amid COVID-19 - Lessons learnt from other QR code digital technologies -- Optimal testing strategies for infectious diseases.s
Keywords: Biomedical engineering; Medical informatics; Medicine, Preventive; Health promotion; Medical and Health Technologies; Health Informatics; Health Promotion and Disease Prevention; Medical Informatics; COVID-19